Livelihood Srategies and the Welfare of Transmigrants - Yanmesli Yanmesli; R Rijanta; Sutikno Sutikno; Nasruddin Harahap (Indonesian Journal of Geography, 2014)
Transmigration is one of the manifestations of artificial human community that is expected to increase thenatural resource utilization activities for welfare in a transmigration location. This paper is to find out the livelihoodstrategies and their effect on transmigrants’ welfare. Results of the study indicates at Stage I (the first 1.5 years), transmigrantsgenerally applied a survival strategy by relying on the living allotment of government. At Stage II (the second1.5 years), a part of them sougth other source of income for establishing their livelihood. At Stage III (the third 2 yearsand afterward), a part of them left the transmigration location, while others have able to survive until the primary commodityof rubber can be productive after the sixth year of cultivation. Welfare is achieved by those that could to applythe livelihood strategies to have the established sources of income outside the transmigrants’ primary commodity, particularlyfrom Pasuruan, East Java Province.